Identity and Cultural Contestation in a Plural Society: The Development of Chinese Education in Malaysia1 - Yao Sua, Tan; Ker Pong, Thock (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2014)
The development of Chinese education in Malaysia has come a long way since the large-scale immigration of the Chinese beginning in the nineteenth century. As a significant minority group in a plural society, the Chinese have shown a great deal of determination to maintain and propagate their cultural identity via the provision of Chinese education amidst the pervasive influence of the Malay language as the main thrust of the nation building process. It is inevitable then that there is a strong element of identity and cultural contestation in the development of Chinese education. This paper examines three issues that illustrate this contestation. The first issue, i.e. the Chinese language movement, involves the recognition of Chinese as an official language of the country in order to legitimize the position of Chinese education within the national mainstream. The second issue involves the preservation of the character of the Chinese primary schools, which entails the use of Chinese as the main medium of instruction as well as the language of administration and wider communication. The last issue pertains to the establishment of a complete system of Chinese education to strengthen the position of Chinese education in the country.